Detection of Porcine Parvovirus 2 (Ungulate Tetraparvovirus 3) Specific Antibodies and Examination of the Serological Profile of an Infected Swine Herd. - Attila Cságola; Zoltán Zádori; István Mészáros; Tamás Tuboly (PLoS ONE)
Porcine parvovirus 2 (PPV2) is a member of a recently discovered group of swine parvoviruses occurring worldwide. It is frequently detected in lung samples suggesting some pathological role of the virus in diseases. To study this possibility an indirect ELISA was developed to detect PPV2 specific antibodies and to examine the serological profile of an infected swine herd where 185 serum samples collected from different age groups including sows were analyzed. According to the results maternal antibody levels decreased until 14 days of age and PPV2 specific antibodies started to rise between 28 to 43 days of age when respiratory signs were also observed in the examined swine herd. At 57 days of age the clinical signs disappeared and a rapid increase of PPV2 specific antibody levels could be measured simultaneously, peaking at 57 days of age. The viraemic status of different age groups was determined by qPCR using serum samples. At least a low level of viraemia was measured in every age group, but higher copy number of PPV2 was only detected at 57 days of age and the level decreased in older age groups. The changes in virus load and antibody levels together with the onset and decrease of clinical signs suggested that PPV2 had a role in the development of respiratory signs.